Mathematics : applications and connections ; course 3 - Collins, William; Frey-Mason, Patricia; Key, McClain; Linda, Dritsas (New York : Glencoe/McGraw-Hill, 1998)
Mathematics and Statistics
2004-05-06
Keywords: Mathematics